Microneedles for Melanoma Therapy: Exploring Opportunities and Challenges - Lufuno Nemakhavhani; Heidi Abrahamse; Sathish Sundar Dhilip Kumar (Pharmaceutics)
Melanoma is a type of skin cancer that originates in the melanocytes, the epidermis’ basal layer. The skin has traditionally been an attractive administration location for drug delivery in tumor therapy, and it is composed of three layers: the outermost stratum corneum (SC), the middle epidermis, and the deepest layer, the dermis. Melanoma can be treated using a variety of methods, such as chemotherapy, surgery, radiotherapy, and biological therapy, but all are expensive and have side effects. Furthermore, the SC is the primary barrier that contributes to the impermeability of the skin, which is a limitation in epidermal drug transport and can aid in achieving effective drug concentration with minimal side effects at the target location. Microneedles (MNs) are tiny needles that are easy to use, inexpensive, and non-toxic. In recent years, MNs have been significantly studied for the treatment of melanoma due to their excellent biocompatibility, minimal invasion, high patient compliance, simple penetration process, and high SC penetration rate. Most notably, MNs can provide efficient and seldom unpleasant delivery carriers and synergistic effectiveness by combining multi-model techniques with immunotherapy, gene therapy, photodynamic therapy (PDT), and photothermal treatment (PTT). This review will focus on biocompatibility, biodegradability, limitations, fabrication materials, release mechanisms, and delivery of the therapeutics of MNs for melanoma treatment.